2019
DOI: 10.15244/pjoes/87101
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Antibiotic-Resistant Airborne Bacteria along Roadsides in Rahim Yar Khan, Pakistan

Abstract: Bioaerosols constitute about 50% of atmospheric aerosols. The organic particles in the bioaerosols may be bacteria, fungi, viruses, toxins, endotoxins, pollens, metabolites, or any other biological materials [1]. Over the last few decades, bioaerosol research has improved significantly because of its adverse impact on human health. These biological origin particles are suspended in the air. In external ambient >30% of all aerosols (>0.2 µm in sizes) are of biological origin. Bioaerosols disperse for considerab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 41 publications
1
9
0
Order By: Relevance
“…The isolated Coliform bacteria and the isolated non-hemolytic Streptococci showed mono-resistance to ceftriaxone and ampicillin, respectively. These findings accord with those published elsewhere, showing high rates of antibiotic resistance to airborne Staphylococci species and Gram-negative bacilli [ 17 , 27 ]. The study in indoor sites of a university in Ghana also found high rates of antibiotic resistance in airborne bacteria that included both Gram-positive cocci and Gram-negative bacilli [ 10 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The isolated Coliform bacteria and the isolated non-hemolytic Streptococci showed mono-resistance to ceftriaxone and ampicillin, respectively. These findings accord with those published elsewhere, showing high rates of antibiotic resistance to airborne Staphylococci species and Gram-negative bacilli [ 17 , 27 ]. The study in indoor sites of a university in Ghana also found high rates of antibiotic resistance in airborne bacteria that included both Gram-positive cocci and Gram-negative bacilli [ 10 ].…”
Section: Discussionsupporting
confidence: 93%
“…We also did not collect and analyze ambient air samples at different seasons of the year. Other studies have found seasonal variation in the bacterial count and antibiotic resistance profiles [17,19,20]. We had planned to do sample collection at different times from 2020 onwards and in different seasons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there are significantly fewer atmospheric microorganisms than there are in the oceans and in the soil, there is still a large enough number of bacteria, fungi, viruses, toxins, endotoxins, pollens, metabolites, or any other biological materials that can affect the atmosphere (1). In urban areas, the vehicular intensity adds to dust suspension with the subsequent addition of bioaerosols which varies greatly at different sites due to different point sources.…”
Section: Introductionmentioning
confidence: 99%
“…Enterococcus spp. and some air borne and food borne pathogenic bacteria at alarming stage (Bhatti et al, 2019;Richwagen et al, 2019;Chatham-Stephens et al, 2019;Mehboob and Abbas 2019;Naz & Pasha 2019;Irum et al, 2019). According to the published data, the mortality rate is about 0.7 million worldwide due to antimicrobial resistance pathogens, which will raise 10 million by 2050 (de Kraker et al, 2019) The data reported by Center of Disease and Control showed about 23,000 mortality rates due to infection caused by antimicrobial resistance annually (Lim et al, 2016).…”
Section: Introductionmentioning
confidence: 99%